TOGGLe, a flexible framework for easily building complex workflows and performing robust large-scale NGS analyses - CGIAR Research Program on Rice (2019)
TOGGLe is a workflow manager designed to be as effortless as possible to use for biologists. Pipelines are easily customizable and supported analyses are reproducible and shareable. It is freely available at http://toggle.southgreen.fr/, and can be deployed onto HPC clusters as well as on local machines.